Implementasi Manajemen Layanan Khusus Bimbingan dan Konseling di Sekolah Dasar - Maulana, Rafli Firzatullah; Rowiari, Destriani Natalia; Cahyanti, Adelia Nasha Fitri; Nurdin, Muhammad Surya Afrizal; Wulandari, Ayu; Nuphanudin, Nuphanudin (ARZUSIN, 2024)
The aim of this research is to analyze the implementation of special guidance service management at SD Negeri 234 Gresik. This type of research is qualitative and uses interview methods with school principals, supervisors and class teachers. The findings show that the implementation of special service management in schools has not been successful. There are several problems such as lack of planning, weak organization, lack of strong mobilization, and lack of control. This means that the support and advice provided may not be optimal. Schools are encouraged to improve planning, organization, mobilization and management to improve the quality of guidance and counseling services for students.